EFEKTIVITAS PERAN LEMBAGA PEMERINTAH DALAM MENANGGULANGI PEREDARAN NARKOTIKA DI DALAM LEMBAGA PEMASYARAKATAN - Arka Candyas Hermawan; Jonathan Ervando; David Njotowidjaja; Rugun Romaida Hutabarat (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study examines narcotics circulation within correctional facilities, which persists due to weak supervision, overcrowding, staff involvement, and high inmate demand. Using a normative juridical approach supported by empirical data, the study analyzes the mechanisms of narcotics distribution and evaluates government efforts involving the Ministry of Law and Human Rights, the National Narcotics Board, and the National Police. The findings indicate that current measures remain ineffective due to structural constraints such as punitive drug policies, limited security infrastructure, and insufficient isolation of high-risk inmates. The study concludes that policy reform, independent oversight, and stronger institutional coordination are essential to curb narcotics circulation in prisons.